HUBUNGAN DAYA LEDAK OTOT LENGAN DAN KEKUATAN OTOT LENGAN TERHADAP KEMAMPUAN CHEST PASS BOLA BASKET SISWA SEKOLAH MENENGAH ATAS NEGERI 2 BANGLAS SELAT PANJANG - Abdul Rasyid; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT. This study is a correlational study. The population in this study were students Senior High School 2 Kelayang, and a sample set of male students, then drawn using purposive stratified sampling technique as much as 25% of each stratum (grade level) in order to obtain the number of 30 samples. Variable data collection techniques explosive power arm muscles (x1) with test Two Hands Medicine Ball Put, variable arm muscle strength with push-up test, and chest pass variables to test the ability of chest pass. This research analyzes using the Pearson product moment correlation formula. Results of calculation of correlation coefficient X1 with Y: X2 with Y values obtained count r> r table. (0.65: 0.59> 0.361) and the correlation coefficient significance testing X1 with Y: X2 with Y obtained F count> F table. (21:17> 3:34). Based on the results obtained can be concluded that there is a significant correlation between muscle explosive power arm and arm muscle strength in the ability of chest pass at 46.24%.Keywords : Explosive power arm muscles, muscle strength of arm, chest pass